2017
DOI: 10.3389/fsurg.2017.00033
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vs. Microscopic Resection of Sellar Lesions—A Matched Analysis of Clinical and Socioeconomic Outcomes

Abstract: BackgroundDirect comparisons of microscopic and endoscopic resection of sellar lesions are scarce, with conflicting reports of cost and clinical outcome advantages.ObjectiveTo determine if the proposed benefits of endoscopic resection are realized on a population level.MethodsWe performed a matched cohort study of 9,670 adult patients in the MarketScan database who underwent either endoscopic or microscopic surgery for sellar lesions. Coarsened matching was applied to estimate the effects of surgical approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Additionally, nonsurgical and surgical cohorts were matched for age groups, sex, and comorbidities with coarsened exact matching, a method that is similar to propensity score matching but reduces model dependence and estimation error. 22,23 All tests were 2-sided and conducted at the .05 level of significance. All analyses were performed with SAS statistical software version 9.4 (SAS Institute Inc) and Stata statistical software version 14 (StataCorp LLC).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, nonsurgical and surgical cohorts were matched for age groups, sex, and comorbidities with coarsened exact matching, a method that is similar to propensity score matching but reduces model dependence and estimation error. 22,23 All tests were 2-sided and conducted at the .05 level of significance. All analyses were performed with SAS statistical software version 9.4 (SAS Institute Inc) and Stata statistical software version 14 (StataCorp LLC).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the above data, several authors have performed level 4 studies that report less favorable cost scenarios for EEAs . Azad et al .…”
Section: Cost Utility Of Esbsmentioning
confidence: 99%
“…In contrast to the above data, several authors have performed level 4 studies that report less favorable cost scenarios for EEAs . Azad et al . completed a level 4 retrospective, observational administrative database study that reported the total index payment was higher for EEA ($32,959) vs microscopic approach ($29,977) and that EEA benefits were not seen at population level.…”
Section: Cost Utility Of Esbsmentioning
confidence: 99%
See 2 more Smart Citations